TiO2 nanoparticles catalysed synthesis of 2-arylbenzimidazoles and 2-arylbenzothiazoles using hydrogen peroxide under ambient light. Issue 2 (22nd January 2016) - Bahrami, Kiumars; Khodaei, Mohammad M.; Naali, Fardin
Abstract : A H2 O2 /TiO2 P25 nanoparticle system has been examined and applied towards synthesis of a wide range of 2-substituted benzimidazole and benzothiazole derivatives from oxidative coupling of aromatic 1, 2-phenylendiamine and 2-aminothiophenol with aromatic aldehydes bearing different types of substituents.